Kemitraan Publik-Privat dalam Pengelolaan Sampah di TPA Tamangapa Kota Makassar - Nahruddin, Zulfan (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2016)
Abstract: This study aims to describe and analyze the implementation of the Government of Makassar partnership with PT. Gikoko Kogyo Indonesia to tackle the problem of waste in the landfill Tamangapa and benefits for the surrounding communities , with a look at the outputs and outcomes of the partnership that exists. This study used qualitative methods or approaches to case study research. As for that to be the case in this study is a case that the formulation of the research problem. Data was collected by observation (observation) directly in the field, in depth interviews, and documentation. Determination conducted purposive informant , the informant saw the fit between the candidate with the required information . Data were analyzed with data reduction, data presentation, and draw conclusions. This study shows that the implementation of the partnership between the government of the city of Makassar with PT. Gikoko Kogyo Indonesia provides an overview and analysis that this partnership is not effective in addressing the problem of waste around the landfill Tamangapa it is seen from the outputs and outcomes achieved the improvement of the environmental conditions of the landfill is only able to reduce the problem of garbage odors coming from the landfill but can not overcome the problems of garbage as a whole. Of the implementation of this partnership also provides benefits to the local community in the form of a reduction in the smell of garbage and lighting lamps in the landfill provide ease of night time activity. Keywords: partnership governance, waste, landfill Tamangapa Abstrak: Penelitian ini bertujuan untuk mendeskripsikan dan menganalisa pelaksanaan kemitraan Pemerintah Kota Makassar dengan PT. Gikoko Kogyo Indonesia dalam mengatasi masalah persampahan di TPA Tamangapa dan manfaatnya bagi masyarakat sekitar, dengan melihat output dan outcome dari kemitraan yang terjalin. Penelitian ini menggunakan metode atau pendekatan kualitatif dengan jenis penelitian studi kasus. adapun yang menjadi kasus dalam penelitian ini yaitu kasus yang menjadi rumusan masalah peneliti. Teknik pengumpulan data dilakukan dengan observasi (pengamatan) langsung dilapangan, wawancara mendalam, dan dokumentasi. Penentuan informan dilakukan secara Purposive, dengan melihat kesesuaian antara calon informan dengan informasi yang dibutuhkan. Data dianalisis dengan reduksi data, penyajian data, dan menarik kesimpulan. Penelitian ini menujukkan bahwa dari pelaksanaan kemitraan antara pemerintah kota makassar dengan PT. Gikoko Kogyo Indonesia memberikan gambaran dan analisa bahwa kemitraan ini tidak efektif dalam mengatasi permasalahan persampahan di sekitar TPA Tamangapa hal ini dilihat dari output dan outcome yang tercapai yakni perbaikan kondisi lingkungan TPA hanya mampu mengurangi masalah bau sampah yang bersumber dari TPA tetapi tidak dapat mengatasi permasalahan sampah secara keseluruhan. Dari pelaksanaan kemitraan ini juga memberikan manfaat bagi masyarakat sekitar berupa pengurangan bau sampah dan penerangan lampu di TPA  memberikan kemudahan beraktifitas dimalam hari. Kata kunci: kemitraan governance, sampah, TPA Tamangapa